Α-Lipoic Acid Ameliorates The Changes In Prooxidant-Antioxidant Balance In Liver And Brain Tissues Of Propylthiouracil- Induced Hypothyroid Rats - Adile Merve Baki; Abdurrahman Fatih Aydın; Pervin Vural; Vakur Olgaç; Semra Doğru Abbasoğlu; Müjdat Uysal (Cell Journal, 2020)
Objective There are controversial data about the prooxidant-antioxidant balance in hypothyroidism. We aimed to investigate the effect of α-lipoic acid (ALA) on oxidative stress parameters in the liver and brain of propylthiouracil (PTU)-induced hypothyroid rats.